Study of the clinical aspect of diabetic foot ulcers and its surgical management - Archana Shukla; Sourabh Mishra (Journal of the Foot & Ankle, 2022)
Objective: Diabetes is a global epidemic and a leading cause of death by disease. It is the common underlying cause of foot ulcers, infection, and ischemia, which are among the most serious complications of diabetes. This work aimed to study the clinical profile, surgical management, and outcome of patients with diabetic foot infections. Methods: Prospective study recruiting patients >18 years of age with diabetic foot infections. All patients underwent a detailed history and clinical examination, being distributed as per their different sociodemographic, clinical, and foot ulcer site characteristics, with further management and evaluation. Results: One hundred patients were recruited, with a mean age of 51.32±11.45 years. Majority of patients (73%) had a lower socioeconomic status. All patients had type 2 diabetes, with male predominance (78%). Mean diabetes mellitus duration was 9.68±5.03 years. Ulcer (92.31%) and discharge (72.31%) were the commonest complaints. During correlation analysis, a strong statistically significant (p<0.001) correlation was observed between amputation and HBA1c level (0.747) and SINBAD score (0.871), while correlation with RBS level was weak (0.532). Commonest presenting site was forefoot, followed by hindfoot. Conclusion: The SINBAD score is simple to use in daily practice, being more effective in describing diabetic foot. Primary and secondary healthcare systems in developing countries have limited resources, using different approaches to manage diabetic foot care. The SINBAD system can be used as a primary screening tool. Provision of correct and convenient footwear and efficient treatment of minor injuries are recommended to downturn ulcer occurrence. Level of Evidence II; Prospective Study; Lesser Quality (eg, patients enrolled at different points in their disease or <80% follow-up).